Implementasi WebGIS untuk Pemetaan Objek Wisata Kota Jakarta Barat dengan Metode Location Based Service menggunakan Google Maps API - I Made Prasatya Mertha; Vincent Simadiputra; Eko Setyawan; Suharjito Suharjito (Universitas Islam Sumatera Utara, 2019)
West Jakarta is one of the cities in the DKI Jakarta province which has great tourism potential, especially on cultural and historical tourism. In the city, there are lots of historical heritage buildings during the Dutch colonial era. However, in fact the information about it is still limited especially for foreign tourists that know more about Bali as Indonesia. One of the methods to introduce the tourism is by using webGIS technology as it is the aim of this research that develop a tourism webGIS of West Jakarta which can be accessed by internet media. By using webGIS, it can be displayed West Jakarta tourisms that equipped with map location point and its travel route, and it can be accessed by internet browser without using GIS-processed software. The displayed tourisms are cultural and historical, culinary, shopping, family and religious tourisms. The webGIS was created by using Location Based Service (LBS) method that utilizes Google Maps API and Framework CodeIgniter. With LBS, the coordinates of tourist locations in the form of lattitude and longitude originating from the Google Maps application can easily be inputed in the webGIS code structure. This WebGIS was successfully accessed through an internet browser both on a computer and smartphone device, and also with usability test by distributing questionnaires to 40 respondents. The questionnaires contain several questions regarding the effectiveness, simplicity, and satisfaction during accessing the webGIS. Based on the results of the questionnaire, it can be concluded that the tourism webGIS application of West Jakarta classified into categories sufficiently effective, simple and satisfying.